Poverty Assessment and Analysis of Factors Affecting Income of the Poor Khmer Households in Loan my Village, Tam Binh District, Vinh Long Province (Global Journal of Human-Social Science, 2016)
Abstract not found
Keywords: income; poor khmer households; situation; support programs